THE INFLUENCE OF TIKTOK’S USES AND GRATIFICATION DIMENSION ON PURCHASE INTENTION FOR SOMETHINC SKINCARE PRODUCTS IN INDONESIA THROUGH CUSTOMER ENGAGEMENT AS AN INTERVENING VARIABLE - Norazizah, Siti; Evanita, Susi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to analyze the effect of TikTok's U&G dimension on purchase intention through customer engagement as the intervening variable. The research method used was a survey with a sample of 343 respondents. The data were statistically analyzed using SEM-PLS. The results showed that information seeking and social sharing are able to influence purchase intention directly or through customer engagement, while entertainment, exposure, and affection are not able to influence purchase intention directly but can influence it through customer engagement. These findings indicate that customer engagement plays a mediating role in the relationship between U&G dimensions and purchase intentions for Soemthinc skincare products. This research provides practical implications for company strategies to consider customer engagement factors to increase purchase intentions. This study has limitations on consumers of skincare products, so the results of the study cannot be generalized to other categories, and it is recommended to use other variables. Keywords: Uses and Gratification; Purchase Intention; Customer Engagement ; Tiktok ; Somethinc